International relations and Islam diverse perspectives - Adiong, Nassef Manabilang (Cambridge Scholars Publishing, 2013)
This work presents the idea of finding a middle way or common ground of understanding between two bodies of knowledge conceived from two different hemispheres of the world; namely, International Relations (IR), a social science discipline conceived in the UK and the US (the West), and Islam or Islamic studies which was conceived in the Arab world and developed in Iran, Pakistan, Turkey, Malaysia, Indonesia, and many non-Arab countries.